2022
DOI: 10.3389/fpls.2022.932594
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering to enhance the accumulation of bioactive flavonoids licochalcone A and echinatin in Glycyrrhiza inflata (Licorice) hairy roots

Abstract: Echinatin and licochalcone A (LCA) are valuable chalcones preferentially accumulated in roots and rhizomes of licorice (Glycyrrhiza inflata). The licorice chalcones (licochalcones) are valued for their anti-inflammatory, antimicrobial, and antioxidant properties and have been widely used in cosmetic, pharmaceutical, and food industries. However, echinatin and LCA are accumulated in low quantities, and the biosynthesis and regulation of licochalcones have not been fully elucidated. In this study, we explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“… 9 Some studies have shown their role in the prevention and treatment of cardiovascular diseases, osteoporosis, diabetes, obesity and menopausal symptoms. 10 , 11 Chemically speaking, osteogenic effects occur through interaction with ERa and ERb, both subtypes of estrogen receptors (ERs) located on the surface of osteoblast cells. They show structural similarity with 17-β-estradiol (E2), which enables them to modulate the mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 Some studies have shown their role in the prevention and treatment of cardiovascular diseases, osteoporosis, diabetes, obesity and menopausal symptoms. 10 , 11 Chemically speaking, osteogenic effects occur through interaction with ERa and ERb, both subtypes of estrogen receptors (ERs) located on the surface of osteoblast cells. They show structural similarity with 17-β-estradiol (E2), which enables them to modulate the mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…While there are many studies in the literature on the anti-inflammatory, antioxidant and anticarcinogenic effects of quercetin, few studies have investigated its effects on the bone. 7 , 9 , 10 , 11 Pang et al aimed to study the effect of quercetin on the differentiation and proliferation of bone marrow mesenchymal stem cells in mice. The results showed that quercetin significantly increased bone marrow mesenchymal stem cell proliferation, alkaline phosphatase activity, extracellular matrix production and mineralization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The versatility of A. rhizogenes strains to infect a range of different plant species is outstanding and can be used both on model and non‐model organisms. For example, overexpression of AtMYB12 , which encodes a master transcriptional regulator of flavonoid biosynthesis in Arabidopsis, in licorice ( Glycyrrhiza inflata ) hairy roots leads to a 2‐ to 5‐fold accumulation of the bioactive flavonoids licochalcone A and echinatin, which have anti‐inflammatory, antimicrobial, and antioxidant properties (Wu et al, 2022). Similarly, overexpression of the leaf color (LC) TF that regulates anthocyanin production in maize and of AtPAP1, a member of the MYB TF family in Arabidopsis, in hairy roots of the Asian medicinal plant Scutellaria baicalensis results in an enhanced total flavone content, especially of baicalin, baicalein, and wogonin, which all have health‐promoting traits (Park et al, 2021).…”
Section: Technologies For Pmementioning
confidence: 99%
“…Because the complex, dimerized TIAs are synthesized in C. roseus leaves, transformation of hairy roots, although useful in genetic characterization, does not allow the investigation of TIA pathway genes that are predominantly expressed in the leaves. Like C. roseus , the generation of stable transgenic plants are difficult and time consuming for many other medicinal plants, such as Glycyrrhiza inflata [ 46 ] which produce the bioactive agent licochalcones. An efficient VIGS technique certainly benefits the studies of the biosynthesis and regulation of the specialized metabolites in these plants.…”
Section: Introductionmentioning
confidence: 99%